THE RELATIONSHIP BETWEEN OLDER PEOPLE’S COGNITIVE FUNCTION AND FAMILY BURDEN (Proceedings OPTIMAL, 2024)
The currently ageing population is affecting an increasing number of older people. Families have a role in caring for older people, but caring for older people can burden families. Families with family burden can have negative impacts such as neglect of older people, decreased care, and family quality of life. This study aims to determine the relationship between the cognitive function of older people and the family burden in caring for older people. This type of research is quantitative research with a cross-sectional design. A sample of 119 respondents was taken with a simple random sampling technique. The instruments used were the Mini-Mental State Examination (MMSE) and Zarit Burden Interview (Z.B.I.), analyzed using Kendall's Tau test. The analysis showed that the majority of older people experienced a mild decline in cognitive function by 46.2%, and the majority of families caring for older people did not experience a burden of 90.8% and obtained a p-value of 0.010 (p